Subunit-subunit interactions are weakened in mutant forms of acetohydroxy acid synthase insensitive to valine inhibition - Kyselková, Martina; Janata, Jiří; Ságová-Marečková, Markéta; Kopecký, Jan (Archives of microbiology, 2010)
In acetohydroxy acid synthase from Streptomyces cinnamonensis mutants affected in valine regulation, the impact of mutations on interactions between the catalytic and the regulatory subunits was examined using yeast two-hybrid system. Mutations in the catalytic and the regulatory subunits were projected into homology models of the respective proteins. Two changes in the catalytic subunit, E139A (alpha domain) and DeltaQ217 (beta domain), both located on the surface of the catalytic subunit dimer, lowered the interaction with the regulatory subunit. Three consecutive changes in the N-terminal part of the regulatory subunit were examined. Changes G16D and V17D in a loop and adjacent alpha-helix of ACT domain affected the interaction considerably, indicating that this region might be in contact with the catalytic subunit during allosteric regulation. In contrast, the adjacent mutation L18F did not influence the interaction at all. Thus, L18 might participate in valine binding or conformational change transfer within the regulatory subunits. Shortening of the regulatory subunit to 107 residues reduced the interaction essentially, suggesting that the C-terminal part of the regulatory subunit is also important for the catalytic subunit binding.
Keywords: Acetolactate Synthase; Valine; Allosteric Regulation; acetolaktátsynthasa; Protein Structure, Secondary; Two-Hybrid System Techniques; valin; alosterická regulace; techniky dvojhybridového systému; Streptomyces; sekundární struktura proteinů